Battery cell, battery device, and electric device

CN123018147APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510553000.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,目前固态电池单体的循环性能仍较差

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018147A_ABST
    Figure CN123018147A_ABST
Patent Text Reader

Abstract

The present disclosure discloses a battery cell, a battery device and a power consumption device. The battery cell of the present disclosure comprises a positive electrode sheet, the positive electrode sheet comprises a current collector and a positive electrode film layer covering at least one side surface of the current collector, the positive electrode film layer comprises a composite positive electrode active material, the composite positive electrode active material comprises a positive electrode active material and a lithium-containing porous material covering at least part of the surface of the positive electrode active material, and the average pore diameter of the lithium-containing porous material is 0.2 nm to 0.8 nm. The radius of lithium ion is smaller than that of transition metal ion and solid-state electrolyte sulfur-based anion. Coating the lithium-containing porous material with the average pore diameter in the above range on at least part of the surface of the positive electrode active material can allow the lithium ion to pass freely while limiting the passage of anions between the transition metal ion and the solid-state electrolyte, reducing the interdiffusion of non-lithium elements between the positive electrode active material and the solid-state electrolyte in the solid-state battery, and improving the cycle performance of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of batteries, and in particular to a battery cell, a battery device, and an electrical device. Background Technology

[0002] Compared to battery cells that use liquid electrolytes, solid-state battery cells use solid electrolyte materials, which makes them less prone to combustion and explosion, and thus have high reliability and high energy density.

[0003] However, the cycle performance of solid-state battery cells is still relatively poor. Summary of the Invention

[0004] This disclosure provides a battery cell, a battery device, and an electrical device that can improve the cycle performance of the battery cell.

[0005] In a first aspect, this disclosure provides a battery cell including a positive electrode sheet, the positive electrode sheet including a current collector and a positive electrode film layer covering at least one side of the current collector, the positive electrode film layer including a composite positive electrode active material, the composite positive electrode active material including a positive electrode active material and a lithium-containing porous material covering at least a portion of the surface of the positive electrode active material, the lithium-containing porous material having an average pore size of 0.2 nm to 0.8 nm.

[0006] The radius of lithium ions is smaller than that of transition metal ions and sulfide anions in solid electrolytes. By coating at least a portion of the surface of the positive electrode active material with lithium-containing porous materials within the aforementioned average pore size range, the passage of transition metal ions and solid electrolyte anions can be restricted while allowing lithium ions to pass freely. This reduces the interdiffusion of non-lithium elements between the positive electrode active material and the solid electrolyte in solid-state batteries. At the same time, lithium ions from the lithium-containing composite molecular sieve material naturally diffuse and migrate, distributing themselves at the interstitial sites of the lithium-containing porous material, thereby enhancing its lithium ion transport capacity and improving the cycle performance of the battery cell.

[0007] In some embodiments, the average pore size of the lithium-containing porous material is 0.2 nm to 0.7 nm.

[0008] The average pore size of lithium-containing porous materials within the above range can better restrict the passage of transition metal ions and solid electrolyte sulfide anions, reduce the interdiffusion between non-lithium elements, while lithium ions can still pass freely, which helps the diffusion of lithium ions and can simultaneously improve the cycle performance and capacity performance of lithium ions.

[0009] In some embodiments, lithium-containing porous materials include those with the molecular formula Li. a M b D c O d G eThe material includes, wherein M comprises one or more of Si, Ti, Al, Zr, P, Mg, Fe, Zn, Cu, and V; D comprises one or more of P, Zr, B, Nb, Ti, and Sr; G comprises one or more of Cl, F, and H; 0≤a≤4, 0≤b≤10, 0≤c≤10, 2<d≤6, and 0≤e≤10.

[0010] Lithium-containing porous materials may include composite molecular sieve materials with the molecular formula Li. a M b D c O d G e In the composite molecular sieve material, atoms represented by the D element occupy atoms represented by the M element, replacing some of the M element atoms, which can form bridging oxygen bonds (MOD). The bond energy is higher than that of single MOM or DOD bonds, and together they form a stable molecular sieve framework structure. This synergistically controls the average pore size of the molecular sieve channels, reduces the diffusion of transition metal ions and solid electrolyte particle anions, and reduces side reactions at the cathode and electrolyte interface. At the same time, the composite molecular sieve material on the surface also includes a reasonable ratio of lithium elements. Lithium ions naturally diffuse and migrate, distributing in the interstitial sites of the molecular sieve. This can improve the continuity of lithium ions between the lithium-containing porous materials of the coating material, improve the lithium ion transport capacity, and reduce the influence of non-lithium molecular sieve coating materials on the lithium ion transport capacity, thereby further improving the cycle performance of the battery cell.

[0011] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, b / c is 1:(0.3~10).

[0012] A b / c (M / D element ratio) value within the above range can achieve an average pore size within the above range, exhibiting good lithium-ion transport capability, which is beneficial for improving cycle performance while maintaining good capacity performance.

[0013] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, b / c is 1:(0.8~1.3).

[0014] Within the above range, the proportion of DO tetrahedral structures formed by atoms of the smaller atomic radius D element increases, the negative charge density on the pore surface increases, and the migration of anions such as S2- can be suppressed by electrostatic repulsion, further reducing the diffusion of sulfide anions in solid electrolytes. At the same time, it has good lithium-ion transport performance, and can obtain battery cells with better cycle performance and capacity performance.

[0015] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, the atoms represented by the M element and the atoms represented by the D element share the oxygen atom.

[0016] The M element represents an atom that shares an oxygen atom with the D element, forming a bridging oxygen bond (MOD). This bond energy is higher than that of a single MOM or DOD bond, which can improve the structure's high-temperature resistance and chemical stability, reducing the likelihood of a Li-based molecular formula. a M b D c O d G e The stability of the material during long-term cycling is improved, reducing shedding from the surface of the positive electrode active material and further enhancing cycling performance.

[0017] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, M includes one or more of Si, Al, and Zr, and D includes one or more of P, Nb, and Sr.

[0018] M and D respectively include the elements mentioned above. The cation radius represented by element M can be larger than that represented by element D. Based on the synergistic adjustment of pore size to obtain a more suitable range of pore size, a hybrid structure of heterogeneous interface can be formed, reducing lattice stress and improving the structural stability of composite molecular sieve materials. At the same time, this structure has a stronger ability to transport lithium ions, which can accelerate lithium ion transport and further improve the cycle performance and capacity of battery cells.

[0019] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, the radius of the cation represented by element M is greater than that represented by element D.

[0020] The large cation radius represented by the M element can expand the framework of the molecular sieve material, resulting in a large pore size. Introducing the small cation radius represented by the D element can reduce the pore size. By controlling the M / D element ratio of the molecular sieve material, the expansion of the composite molecular sieve framework can be limited, resulting in a composite molecular sieve material with a more suitable pore size range, which helps to further improve the cycle performance.

[0021] In some embodiments, the structure of the lithium-containing porous material includes at least one of a tetrahedral structure, a hexahedral structure, and an octahedral structure.

[0022] The structures of lithium-containing porous materials include the aforementioned polyhedral structures, which can form three-dimensional interconnected channels, increasing the tortuosity of ion diffusion paths, making it more difficult for transition metal ions and chalcogenide anions to pass through lithium-containing porous materials, and limiting their diffusion ability.

[0023] In some embodiments, the structure of the lithium-containing porous material includes a first tetrahedral structure and a second tetrahedral structure. The first tetrahedral structure and the second tetrahedral structure each independently include at least one of silicon-oxygen tetrahedral structure, phosphorus-oxygen tetrahedral structure, aluminum-oxygen tetrahedral structure, zirconium-oxygen tetrahedral structure, and titanium-oxygen tetrahedral structure. The central atoms of the first tetrahedral structure and the second tetrahedral structure are different.

[0024] Atoms represented by element D occupy atoms represented by element M, replacing some atoms represented by element M. For example, a phosphorus-oxygen tetrahedron squeezes out some silicon-oxygen tetrahedra. The two tetrahedra have different volumes, and their ratio can be adjusted to regulate the average pore size of lithium-containing porous materials, making them more flexible.

[0025] Meanwhile, on the one hand, the structures of lithium-containing porous materials include different types of first tetrahedral structures such as Zr-O tetrahedrons and second tetrahedral structures such as PO tetrahedrons. First tetrahedrons have higher bond energies, providing skeletal rigidity, while second tetrahedral structures offer better flexibility, enhancing local structural toughness. The combination of these two structures can better adapt to the volume expansion of the positive electrode active material, improving the structural stability and interfacial stability of lithium-containing porous materials. On the other hand, the sharing of vertices or edges between first and second tetrahedral structures can form a heterogeneous pore network. The first tetrahedron structure acts as a "node," expanding the main pores, improving rapid lithium-ion transport, and reducing polarization. The second tetrahedron structure acts as a "barrier," forming sub-nanometer bottlenecks locally, blocking transition metal ions and sulfide anions. This helps to further improve the cycle performance of individual battery cells.

[0026] In some embodiments, the lithium-containing porous material includes: a framework structure including a plurality of pores; and a filling portion filling at least a portion of the pores in the framework structure, the filling portion comprising a lithium-containing compound.

[0027] The aforementioned lithium-containing porous materials include a framework structure and a filling portion. The framework structure provides a porous environment for the molecular sieve material. The lithium-containing compound fills the porous structure of the framework structure. On the one hand, it can help support the framework and improve the structural stability of the lithium-containing porous material. On the other hand, the lithium-containing compound filled in the pores forms a "bottleneck effect" with the framework pore size, and works synergistically with the framework to regulate the pore size of the lithium-containing porous material being coated. Through pore size deformation, while allowing lithium ions to pass freely, it can restrict the passage of transition metal ions and anions between solid electrolytes, reduce the interdiffusion of non-lithium elements between the positive electrode active material and the solid electrolyte in solid batteries, and improve the cycle performance of the battery cell.

[0028] In some embodiments, the framework structure includes one or more of titanium dioxide, zirconium dioxide, aluminum oxide, silicon dioxide, aluminosilicate, phosphoaluminate, metal-organic frameworks, and covalent organic frameworks.

[0029] The aforementioned framework structures have a porous structure similar to molecular sieves, which can provide a porous structure with good stability, thus helping to improve the cycle performance of battery cells.

[0030] In some embodiments, the lithium-containing compound includes one or more of lithium halides, lithium oxide, lithium hydroxide, and lithium oxyacids.

[0031] The aforementioned lithium-containing compounds can provide freely moving lithium ions, improve the lithium-ion transport performance of lithium-containing porous materials, and thus improve the cycle performance and discharge capacity of battery cells.

[0032] In some embodiments, the oxycarbonate includes one or more of lithium phosphate, lithium zirconate, lithium borate, lithium niobate, and lithium titanate.

[0033] In some embodiments, the mass fraction of lithium-containing porous material is 0.05% to 1%, based on a mass fraction of 100% for the positive electrode active material.

[0034] When the mass fraction of lithium-containing porous materials is within the above range, it can reduce the interdiffusion of elements between the positive electrode active material and the solid electrolyte particles, while also improving the integrity of the coating layer and the pore connectivity. Furthermore, it can balance ion sieving and lithium-ion flux, resulting in battery cells with excellent cycle performance and discharge capacity.

[0035] In some embodiments, the positive electrode active material includes Li f Ni g Co h Mn i O j J kOne or more of lithium transition metal oxides and their modified compounds, 0.5≤f≤1.2, 0.5≤g≤0.97, 0.1≤h≤0.2, 0.1≤i≤0.3, 1≤j≤2, 0≤k≤1, and J includes one or more of N, F, S and Cl.

[0036] Lithium transition metal oxides are prone to the dissolution of transition metal ions, resulting in significant interdiffusion issues between the positive electrode active material and the solid electrolyte. The application of the lithium-containing porous material with the above structure to a system using lithium transition metal oxides as the positive electrode active material can better improve cycle performance.

[0037] In some embodiments, the mass content of the composite positive electrode active material is 60% to 90%, with the total mass content of the positive electrode film layer being 100%.

[0038] In some embodiments, the positive electrode film layer further includes a sulfide electrolyte, with the total mass content of the positive electrode film layer being 100%, and the mass content of the sulfide electrolyte particles in the positive electrode film layer being 5% to 30%.

[0039] When the mass content of the composite positive electrode active material and the mass content of the sulfide electrolyte particles are within the above range, the battery has both high energy density and long cycle life.

[0040] In some embodiments, the battery cell further includes a solid electrolyte layer, the solid electrolyte layer comprising the chemical formula Li 10±δ5 Ge 1-m R m P 2-q Q q S 12-n W n The electrolyte material has the following properties: 0≤δ5<9, 0≤m≤1, 0≤q≤2, 0≤n<1, R includes one or both of Si and Sn, Q includes Sb, and W includes one or more of O, Se, Te, Cl, Br, I and F.

[0041] Secondly, embodiments of this disclosure provide a composite positive electrode active material, comprising a positive electrode active material and a lithium-containing porous material coating at least a portion of the surface of the positive electrode active material, wherein the average pore size of the lithium-containing porous material is 0.2 nm to 0.8 nm.

[0042] Thirdly, embodiments of this disclosure provide a battery device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure.

[0043] Fourthly, embodiments of this disclosure provide an electrical device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure or a battery device according to any embodiment of the third aspect of this disclosure. Attached Figure Description

[0044] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0045] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of the present disclosure;

[0046] Figure 2 This is a schematic diagram of an electrical device according to one embodiment of the present disclosure.

[0047] The following is an explanation of the reference numerals in the attached diagram: 5. Battery cell;

[0048] The accompanying drawings are not necessarily drawn to scale. Detailed Implementation

[0049] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery module, battery cell, battery assembly, and power-consuming device of this disclosure. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this disclosure and are not intended to limit the subject matter of the claims.

[0050] The "range" disclosed in this disclosure is defined by a lower limit and an upper limit, whereby a given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values ​​1 and 2 are listed, and if maximum range values ​​3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0051] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.

[0052] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.

[0053] Unless otherwise specified, all steps of this disclosure may be performed sequentially or randomly, preferably sequentially. For example, if a method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if it is mentioned that the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0054] Unless otherwise specified, in this disclosure, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0055] In this disclosure, the terms "multiple" or "a variety" refer to two or more kinds.

[0056] In the description of the embodiments of this disclosure, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0057] Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C.

[0058] The battery cells mentioned in the embodiments of this disclosure are capable of charging and discharging independently. The battery cells may be cylindrical, cuboid, or other shapes, and this disclosure does not limit this. Figure 1 The example shown is a rectangular battery cell 5.

[0059] The battery cells provided in the embodiments of this disclosure may include, but are not limited to, lithium battery cells and sodium battery cells, such as lithium-ion battery cells, sodium-ion battery cells, lithium metal battery cells, sodium metal battery cells, etc. The battery cells provided in the embodiments of this disclosure include electrode assemblies.

[0060] The electrode assembly can be a wound structure or a stacked structure, and this disclosure does not limit this. The battery cell also includes an outer packaging, which can be used to encapsulate the electrode assembly. The outer packaging can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, such as one or more of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0061] The battery apparatus mentioned in the embodiments of this disclosure may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple battery cells connected in series, parallel, or mixed connections via a busbar. In some embodiments, the battery cell assembly is typically formed by arranging multiple battery cells.

[0062] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.

[0063] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.

[0064] As an example, the battery cell assembly can be a battery module, which can be housed in a housing by fixing the battery module in the housing.

[0065] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.

[0066] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.

[0067] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.

[0068] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.

[0069] The technical solutions described in this disclosure are applicable to various electrical devices that use battery cells or battery devices, such as, but not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. Battery cells and battery devices are used to store or provide electrical energy.

[0070] Figure 2 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc.

[0071] Interdiffusion between the positive electrode active material and the solid electrolyte in solid-state batteries is one of the core interface problems restricting their performance. During cycling, transition metal ions in the positive electrode active material tend to migrate to the sulfide electrolyte, while anions such as sulfur and oxygen in the electrolyte diffuse back to the positive electrode lattice. This bidirectional diffusion is driven by the chemical potential gradient at high-temperature solid-phase contact, forming an interdiffusion layer and a space charge layer at the interface, which can lead to the following effects: a surge in interface impedance, blocking the lithium-ion transport path and resulting in a significant polarization effect; lattice distortion in the positive electrode active material, with the layered structure transforming into a spinel phase, leading to capacity decay; and a decrease in electrolyte ionic conductivity. Simultaneously, byproducts generated by interdiffusion (Li₂S, Li₃P, etc.) accelerate interface degradation, affecting the battery's cycle performance.

[0072] In view of the above problems, this disclosure proposes a battery cell that can improve the cycle performance of solid-state battery cells.

[0073] This disclosure provides a battery cell including a positive electrode sheet, the positive electrode sheet including a current collector and a positive electrode film layer covering at least one side of the current collector, the positive electrode film layer including a composite positive electrode active material, the composite positive electrode active material including a positive electrode active material and a lithium-containing porous material covering at least a portion of the surface of the positive electrode active material, the lithium-containing porous material having an average pore size of 0.2 nm to 0.8 nm.

[0074] The radius of lithium ions is smaller than that of transition metal ions and sulfide anions in solid electrolytes. By coating at least a portion of the surface of the positive electrode active material with lithium-containing porous materials within the aforementioned average pore size range, the passage of transition metal ions and solid electrolyte anions can be restricted while allowing lithium ions to pass freely. This reduces the interdiffusion of non-lithium elements between the positive electrode active material and the solid electrolyte in solid-state batteries. At the same time, lithium ions from the lithium-containing composite molecular sieve material naturally diffuse and migrate, distributing themselves at the interstitial sites of the lithium-containing porous material, thereby enhancing its lithium ion transport capacity and improving the cycle performance of the battery cell.

[0075] For example, the average pore size of the lithium-containing porous material can be 0.2nm, 0.25nm, 0.3nm, 0.35nm, 0.4nm, 0.45nm, 0.5nm, 0.55nm, 0.6nm, 0.65nm, 0.7nm, 0.75nm, 0.8nm, or any range of two of the above values.

[0076] The technical solutions of the embodiments disclosed herein will be described in detail below.

[0077] [Positive electrode plate]

[0078] In some embodiments, the average pore size of the lithium-containing porous material is 0.2 nm to 0.7 nm, optionally 0.3 nm to 0.6 nm, optionally 0.3 nm to 0.5 nm, or optionally 0.32 nm to 0.4 nm.

[0079] The average pore size of lithium-containing porous materials within the above range can better restrict the passage of transition metal ions and solid electrolyte sulfide anions, reduce the interdiffusion between non-lithium elements, while lithium ions can still pass freely, which helps the diffusion of lithium ions and can simultaneously improve the cycle performance and capacity performance of lithium ions.

[0080] For example, the average pore size of the lithium-containing porous material can be 0.2nm, 0.25nm, 0.3nm, 0.35nm, 0.4nm, 0.45nm, 0.5nm, 0.55nm, 0.6nm, 0.65nm, 0.7nm, or any combination of two of the above values.

[0081] In some embodiments, lithium-containing porous materials include those with the molecular formula Li. a M b D c O d G e The material includes, wherein M comprises one or more of Si, Ti, Al, Zr, P, Mg, Fe, Zn, Cu, and V; D comprises one or more of P, Zr, B, Nb, Ti, and Sr; G comprises one or more of Cl, F, and H; 0≤a≤4, 0≤b≤10, 0≤c≤10, 2<d≤6, and 0≤e≤10.

[0082] Lithium-containing porous materials may include composite molecular sieve materials with the molecular formula Li. a M b D c O d G e In the composite molecular sieve material, atoms represented by the D element occupy atoms represented by the M element, replacing some of the M element atoms to form bridging oxygen bonds (MOD). The bond energy is higher than that of single MOM or DOD bonds, collectively forming a stable molecular sieve framework structure. The molecular sieve framework structure has good stability and can also synergistically control the average pore size of the molecular sieve channels, reducing the diffusion of transition metal ions and solid electrolyte particle anions, and reducing side reactions at the cathode and electrolyte interface. At the same time, the composite molecular sieve material on the surface also includes a reasonable ratio of lithium elements. Lithium ions naturally diffuse and migrate, distributing in the interstitial sites of the molecular sieve. This can improve the continuity of lithium ions between the lithium-containing porous materials of the coating material, improve the lithium ion transport capacity, and reduce the influence of non-lithium molecular sieve coating materials on the lithium ion transport capacity, thereby further improving the cycle performance of the battery cell.

[0083] For example, 'a' can be 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or a range of any two of the above values.

[0084] For example, b can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range of any two of the above values.

[0085] For example, c can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range of any two of the above values.

[0086] For example, d can be 2.1, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, or a range of any two of the above values.

[0087] For example, e can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or a range of any two of the above values.

[0088] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, the radius of the cation represented by element M is greater than that represented by element D.

[0089] The large cation radius represented by the M element can expand the framework of the molecular sieve material, resulting in a large pore size. Introducing the small cation radius represented by the D element can reduce the pore size. By controlling the M / D element ratio of the molecular sieve material, the expansion of the composite molecular sieve framework can be limited, resulting in a composite molecular sieve material with a more suitable pore size range, which helps to further improve the cycle performance.

[0090] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, b / c is 1: (0.3~10), optional 1: (0.6~5), optional 1: (0.8~2), optional 1: (0.8~1.4), optional 1: (0.8~1.3), optional 1: (1~2).

[0091] A b / c (M / D element ratio) value within the above range can achieve an average pore size within the above range, exhibiting good lithium-ion transport capability, which is beneficial for achieving good capacity performance while improving cycle performance. When b / c > 1, the MO framework dominates, forming a larger pore size. Although Li+ can pass through, the barrier to transition metal ions is weak. When b / c < 1, the proportion of DO structure increases, the pore size decreases, and the lithium-ion diffusion capability is weak.

[0092] For example, b / c can be 1:0.3, 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range of any two of the above values.

[0093] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, b / c is 1:(0.8~1.3).

[0094] Within the above range, the proportion of DO tetrahedral structures formed by atoms of the smaller atomic radius D element increases, the negative charge density on the pore surface increases, and the migration of anions such as S2- can be suppressed by electrostatic repulsion, further reducing the diffusion of sulfide anions in solid electrolytes. At the same time, it has good lithium-ion transport performance, and can obtain battery cells with better cycle performance and capacity performance.

[0095] For example, b / c can be 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3 or a range of any two of the above values.

[0096] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, the atoms represented by the M element and the atoms represented by the D element share the oxygen atom.

[0097] The M element represents an atom that shares an oxygen atom with the D element, forming a bridging oxygen bond (MOD). This bond energy is higher than that of a single MOM or DOD bond, which can improve the structure's high-temperature resistance and chemical stability, reducing the likelihood of a Li-based molecular formula. a M b D c O d G eThe stability of the material during long-term cycling is improved, reducing shedding from the surface of the positive electrode active material and further enhancing cycling performance.

[0098] In some embodiments, the molecular formula is Li a M b D c O d G e In the material, M includes one or more of Si, Al, and Zr, and D includes one or more of P, Nb, and Sr.

[0099] M and D respectively include the elements mentioned above. The cation radius represented by element M can be larger than that represented by element D. Based on the synergistic adjustment of pore size to obtain a more suitable range of pore size, a hybrid structure of heterogeneous interface can be formed, reducing lattice stress and improving the structural stability of composite molecular sieve materials. At the same time, this structure has a stronger ability to transport lithium ions, which can accelerate lithium ion transport and further improve the cycle performance and capacity of battery cells.

[0100] In some embodiments, the structure of the lithium-containing porous material includes at least one of a tetrahedral structure, a hexahedral structure, and an octahedral structure.

[0101] The structures of lithium-containing porous materials include the aforementioned polyhedral structures, which can form three-dimensional interconnected channels, increasing the tortuosity of ion diffusion paths, making it more difficult for transition metal ions and chalcogenide anions to pass through lithium-containing porous materials, and limiting their diffusion ability.

[0102] In some embodiments, the structure of the lithium-containing porous material includes a first tetrahedral structure and a second tetrahedral structure. The first tetrahedral structure and the second tetrahedral structure each independently include at least one of silicon-oxygen tetrahedral structure, phosphorus-oxygen tetrahedral structure, aluminum-oxygen tetrahedral structure, zirconium-oxygen tetrahedral structure, and titanium-oxygen tetrahedral structure. The central atoms of the first tetrahedral structure and the second tetrahedral structure are different.

[0103] Atoms represented by element D occupy atoms represented by element M, replacing some atoms represented by element M. For example, a phosphorus-oxygen tetrahedron squeezes out some silicon-oxygen tetrahedra. The two tetrahedra have different volumes, and their ratio can be adjusted to regulate the average pore size of lithium-containing porous materials, making them more flexible.

[0104] Meanwhile, on the one hand, the structures of lithium-containing porous materials include different types of first tetrahedral structures such as Zr-O tetrahedrons and second tetrahedral structures such as PO tetrahedrons. First tetrahedrons have higher bond energies, providing skeletal rigidity, while second tetrahedral structures offer better flexibility, enhancing local structural toughness. The combination of these two structures can better adapt to the volume expansion of the positive electrode active material, improving the structural stability and interfacial stability of lithium-containing porous materials. On the other hand, the sharing of vertices or edges between first and second tetrahedral structures can form a heterogeneous pore network. The first tetrahedron structure acts as a "node," expanding the main pores, improving rapid lithium-ion transport, and reducing polarization. The second tetrahedron structure acts as a "barrier," forming sub-nanometer bottlenecks locally, blocking transition metal ions and sulfide anions. This helps to further improve the cycle performance of individual battery cells.

[0105] In some embodiments, the lithium-containing porous material includes: a framework structure including a plurality of pores; and a filling portion filling at least a portion of the pores in the framework structure, the filling portion comprising a lithium-containing compound.

[0106] The aforementioned lithium-containing porous materials include a framework structure and a filling portion. The framework structure provides a porous environment for the molecular sieve material. The lithium-containing compound fills the porous structure of the framework structure. On the one hand, it can help support the framework and improve the structural stability of the lithium-containing porous material. On the other hand, the lithium-containing compound filled in the pores forms a "bottleneck effect" with the framework pore size, and works synergistically with the framework to regulate the pore size of the lithium-containing porous material being coated. Through pore size deformation, while allowing lithium ions to pass freely, it can restrict the passage of transition metal ions and anions between solid electrolytes, reduce the interdiffusion of non-lithium elements between the positive electrode active material and the solid electrolyte in solid batteries, and improve the cycle performance of the battery cell.

[0107] In some embodiments, the framework structure includes one or more of titanium dioxide, zirconium dioxide, aluminum oxide, silicon dioxide, aluminosilicate, phosphoaluminate, metal-organic frameworks, and covalent organic frameworks.

[0108] The aforementioned framework structures have a porous structure similar to molecular sieves, which can provide a porous structure with good stability, thus helping to improve the cycle performance of battery cells.

[0109] In some embodiments, the lithium-containing compound includes one or more of lithium halides, lithium oxide, lithium hydroxide, and lithium oxyacids.

[0110] The aforementioned lithium-containing compounds can provide freely moving lithium ions, improve the lithium-ion transport performance of lithium-containing porous materials, and thus improve the cycle performance and discharge capacity of battery cells.

[0111] In some embodiments, the oxycarbonate includes one or more of lithium phosphate, lithium zirconate, lithium borate, lithium niobate, and lithium titanate.

[0112] In some embodiments, the mass fraction of lithium-containing porous material is 0.05% to 1%, based on a mass fraction of 100% for the positive electrode active material.

[0113] When the mass fraction of lithium-containing porous materials is within the above range, it can reduce the interdiffusion of elements between the positive electrode active material and the solid electrolyte particles, while also improving the integrity of the coating layer and the pore connectivity. Furthermore, it can balance ion sieving and lithium-ion flux, resulting in battery cells with excellent cycle performance and discharge capacity.

[0114] For example, the mass fraction of the lithium-containing porous material can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, or a range of any two of the above values.

[0115] In some embodiments, the positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds.

[0116] Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, lithium titanium oxides, and their respective modified compounds. Lithium transition metal oxides may include, but are not limited to, layered structures and spinel structures.

[0117] Examples of lithium phosphates may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and one or more of their respective modified compounds.

[0118] In some embodiments, the positive electrode active material includes Li f Ni g Co h Mn i O j J k One or more of lithium transition metal oxides and their modified compounds, 0.5≤f≤1.2, 0.5≤g≤0.97, 0.1≤h≤0.2, 0.1≤i≤0.3, 1≤j≤2, 0≤k≤1, and J includes one or more of N, F, S and Cl.

[0119] Lithium transition metal oxides are prone to the dissolution of transition metal ions, resulting in significant interdiffusion issues between the positive electrode active material and the solid electrolyte. The application of the lithium-containing porous material with the above structure to a system using lithium transition metal oxides as the positive electrode active material can better improve cycle performance.

[0120] For example, f can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2 or a range of any two of the above values.

[0121] For example, g can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.97 or a range of any two of the above values.

[0122] For example, h can be 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or a range of any two of the above values.

[0123] For example, i can be 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, or a range of any two of the above values.

[0124] For example, j can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or a range of any two of the above values.

[0125] For example, k can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or a range of any two of the above values.

[0126] In some embodiments, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, and LiNi 1 / 2 Mn 1 / 2 O2, LiMn2O4, Li 4 / 3 Ti 5 / 3 O4, LiNi 1 / 2 Mn 1 / 2 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.80 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.

[0127] In some embodiments, the mass content of the composite positive electrode active material is 60% to 90%, with the total mass content of the positive electrode film layer being 100%.

[0128] For example, the mass content of the composite positive electrode active material can be 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, or any range of two of the above values.

[0129] In some embodiments, the positive electrode film layer further includes a sulfide electrolyte, with the total mass content of the positive electrode film layer being 100%, and the mass content of the sulfide electrolyte particles in the positive electrode film layer being 5% to 30%.

[0130] When the mass content of the composite positive electrode active material and the mass content of the sulfide electrolyte particles are within the above range, the battery has both high energy density and long cycle life.

[0131] For example, the mass content of sulfide electrolyte particles in the positive electrode film layer can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any range of two of the above values.

[0132] The present disclosure provides a composite positive electrode active material, comprising a positive electrode active material and a lithium-containing porous material coating at least a portion of the surface of the positive electrode active material, wherein the average pore size of the lithium-containing porous material is 0.2 nm to 0.8 nm.

[0133] In some embodiments, the positive electrode film layer further includes a positive electrode conductive agent, which may include, but is not limited to, one or more of conductive graphite (such as KS-6, SFG-6), superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0134] In some embodiments, the positive electrode film layer further includes a positive electrode binder, which may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, water-soluble unsaturated resin SR-B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene-butadiene rubber (SBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), fluororubber, and acrylate rubber, or one or more of these.

[0135] [Negative electrode plate]

[0136] In some embodiments, the battery cell further includes a negative electrode sheet, which may include one or more of lithium, lithium alloy, natural graphite, artificial graphite, mesophase micro carbon spheres, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and metal oxides.

[0137] Optionally, the mass fraction of lithium in the lithium alloy can be above 90%.

[0138] Optionally, other elements in the lithium alloy may include, but are not limited to, one or more of In, Mg, Al, Zn, Sn, Ag, Au, Ga, Pt, and Fe.

[0139] Alternatively, the lithium alloy may include, but is not limited to, Li-In alloy, Li-Mg alloy, Li-Al alloy, Li-Zn alloy, Li-Fe alloy, etc.

[0140] Optionally, the silicon-based material may include, but is not limited to, one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0141] Optionally, the tin-based material may include, but is not limited to, one or more of elemental tin, tin oxide, and tin alloy materials.

[0142] Optionally, the metal oxide may be one or more of TiO2, MoO2, In2O3, Al2O3, Cu2O, VO2, Ga2O3, Sb2O5, and Bi2O5.

[0143] In some embodiments, the negative electrode sheet may further include a negative electrode binder, which may include, but is not limited to, one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, carboxymethyl cellulose (CMC), styrene-butadiene rubber, fluororubber, and acrylate rubber.

[0144] In some embodiments, the negative electrode sheet may include a negative electrode conductive agent, which may include, but is not limited to, one or more of conductive graphite (such as KS-6, SFG-6), superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0145] [Solid electrolyte layer]

[0146] In some embodiments, the solid electrolyte includes one or more of sulfide electrolytes, halide electrolytes, and oxide solid electrolyte materials.

[0147] In some embodiments, the battery cell further includes a solid electrolyte layer, which includes a sulfide electrolyte.

[0148] In some embodiments, the sulfide electrolyte may include, but is not limited to, one or more of the following sulfide solid electrolyte materials: silver-germanium sulfide type, LGPS type, lithium sulfide-phosphorus pentasulfide complex type.

[0149] In some embodiments, the battery cell further includes a solid electrolyte layer, the solid electrolyte layer comprising the chemical formula Li 10±δ5 Ge 1-m R m P 2-q Q q S 12-n W n The electrolyte material has the following properties: 0≤δ5<9, 0≤m≤1, 0≤q≤2, 0≤n<1, R includes one or both of Si and Sn, Q includes Sb, and W includes one or more of O, Se, Te, Cl, Br, I and F.

[0150] In some embodiments, as an example, the sulfide solid electrolyte material may include Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 Li3PS4, Li7P3S 11 , Li2S-GeS2, Li2S-P2S5, Li2S-SiS 2、 One or more of Li2S-MeS2-P2S5 (Me = Si, Ge, Sn, Al, etc.).

[0151] In some embodiments, the solid electrolyte layer may further include an adhesive. Optionally, the adhesive may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), styrene-butadiene rubber (SBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), fluororubber, and acrylate rubber.

[0152] Example

[0153] The following embodiments describe the contents disclosed in this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0154] Example 1

[0155] 1. Preparation of positive electrode sheet

[0156] Preparation of composite positive electrode active material: ZrOCl2 and (NH4)2HPO4 precursors, LiOH (molar amount three times that of (NH4)2HPO4), and ternary positive electrode material LiNi are combined. 0.8 Co 0.1 Mn 0.1The mixture was mixed with O2 and ball-milled at 300 rpm for 12 hours, followed by annealing at 500℃ for 6 hours in an oxygen atmosphere to obtain a composite positive electrode active material. At least part of the surface of the ternary positive electrode material was coated with a composite molecular sieve Li. 1.8 ZrP 0.6 O 4.4 The molar ratio of Zr to P (Zr:P) is 1:0.6.

[0157] The above-mentioned composite positive electrode active material is uniformly mixed with sulfide electrolyte Li6PS5Cl and conductive agent VGCF at a mass ratio of 70:27:3 for 10 minutes to obtain composite positive electrode powder. Then, PTFE binder equivalent to 1% of the mass ratio of the first two is added and rolled into a positive electrode film to obtain a positive electrode sheet.

[0158] 2. Preparation of negative electrode sheet

[0159] Mold battery system - lithium-indium alloy, in which the molar ratio of Li to In is 1:3.

[0160] 3. Solid electrolyte layer

[0161] The sulfide solid electrolyte Li6PS5Cl was selected.

[0162] 4. Battery manufacturing

[0163] In the molded battery system, the battery is pressed into shape under a pressure of 10 MPa in the order of positive electrode layer, electrolyte layer and negative electrode layer from top to bottom, and then sealed in the molded battery fixture with an external pressure of 50 MPa.

[0164] The test used a solid-state mold battery with no current collectors on the positive and negative electrode sides. The positive electrode film in the above embodiment can be understood as a positive electrode film layer.

[0165] Examples 2-5

[0166] Lithium-ion battery cells were prepared using a method similar to that in Example 1. The differences from Example 1 were the different amounts of the precursors ZrOCl2 and (NH4)2HPO4, the three-fold molar amount of LiOH compared to (NH4)2HPO4, and the different molar ratio of Zr to P in the resulting composite molecular sieve. Specific values ​​are shown in Table 1.

[0167] Example 6

[0168] Lithium-ion battery cells were prepared using a method similar to that in Example 1, except that the types of elements in the composite molecular sieve were different from those in Example 1.

[0169] Example 6: Preparation of composite positive electrode active material: The precursor (NH4)2HPO4 was replaced with ammonium borate (NH4HB4O7·3H2O), the molar amount of LiOH was 0.75 times the molar amount of ammonium borate, and the precursor ratio was controlled so that the molar ratio of Zr to B in the obtained composite molecular sieve was 1:1.2.

[0170] Comparative Example 1

[0171] Lithium-ion battery cells were prepared using a method similar to that in Example 1. The difference from Example 1 is that the ternary cathode material was not coated with a composite molecular sieve, and the cathode active material was LiNi. 0.8 Co 0.1 Mn 0.1 O2;

[0172] The above-mentioned positive electrode active material is mixed with sulfide electrolyte Li6PS5Cl and conductive agent VGCF at a mass ratio of 70:27:3 for 10 minutes to obtain composite positive electrode powder. Then, PTFE binder equivalent to 1% of the mass ratio of the first two is added and rolled into a positive electrode film to obtain a positive electrode sheet.

[0173] Comparative Example 2

[0174] Preparation of composite positive electrode active material: A conventional molecular sieve, Soconi-Mobil zeolite molecular sieve No. 5 (ZSM-5), is combined with a ternary positive electrode material, LiNi. 0.8 Co 0.1 Mn 0.1 O2 was mixed and ball-milled at 300 rpm for 12 h, followed by annealing at 500 °C for 6 h in an oxygen atmosphere to obtain a composite positive electrode active material. At least part of the surface of the ternary positive electrode material was coated with molecular sieve ZSM-5.

[0175] Performance testing

[0176] 1. The average pore size of the composite molecular sieve is tested as follows: the lattice fringes of the coating layer are observed under a high-resolution electron microscope (HRTEM) to measure the lattice spacing, and then the average pore size for ion migration is calculated.

[0177] 2. Electrochemical Performance: The assembled battery was subjected to charge-discharge tests on the Blue Battery Test Platform at a test temperature of 25℃ and a charge-discharge voltage range of 2.6–4.3V vs. Li. + / Li. Cyclic test procedure: After charging and discharging the full battery at 0.1C for one cycle, record the discharge specific capacity at 0.1C, and then continue charging and discharging at 0.3C. Divide the discharge specific capacity of the 201st cycle by the discharge specific capacity of the 2nd cycle to obtain the capacity retention rate of the 200th cycle at 0.3C.

[0178] The performance test results are shown in Table 1.

[0179] Table 1

[0180]

[0181]

[0182] The composite positive electrode active material of this disclosure includes a positive electrode active material and a lithium-containing composite molecular sieve material coating at least part of the surface of the positive electrode active material. The lithium-containing composite molecular sieve material is porous, and as a lithium-containing porous material, its average pore size is 0.2 nm to 0.8 nm. It can allow lithium ions to pass freely while restricting the passage of transition metal ions and anions between solid electrolytes, thereby reducing the interdiffusion of non-lithium elements between the positive electrode active material and the solid electrolyte in solid batteries. At the same time, lithium ions in the lithium-containing composite molecular sieve material naturally diffuse and migrate, distributing in the interstitial sites of the molecular sieve, thereby improving its lithium ion transport capacity and jointly improving the cycle performance of the battery cell.

[0183] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present disclosure, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. A battery cell, characterized in that, The device includes a positive electrode sheet, which includes a current collector and a positive electrode film layer covering at least one side of the current collector. The positive electrode film layer includes a composite positive electrode active material, which includes a positive electrode active material and a lithium-containing porous material covering at least a portion of the surface of the positive electrode active material. The average pore size of the lithium-containing porous material is 0.2 nm to 0.8 nm.

2. The battery cell according to claim 1, characterized in that, The lithium-containing porous material includes materials with the molecular formula Li. a M b D c O d G e The material includes, wherein M comprises one or more of Si, Ti, Al, Zr, P, Mg, Fe, Zn, Cu, and V; D comprises one or more of P, Zr, B, Nb, Ti, and Sr; G comprises one or more of Cl, F, and H; 0 ≤ a ≤ 4; 0 ≤ b ≤ 10; 0 ≤ c ≤ 10; 2 < d ≤ 6; and 0 ≤ e ≤ 10.

3. The battery cell according to claim 2, characterized in that, The molecular formula is Li a M b D c O d G e In the material, b / c is 1:(0.3~10).

4. The battery cell according to any one of claims 2 to 3, characterized in that, The molecular formula is Li a M b D c O d G e In the material, b / c is 1:(0.8~1.3).

5. The battery cell according to any one of claims 2 to 4, characterized in that, The molecular formula is Li a M b D c O d G e In the material, M includes one or more of Si, Al, and Zr, and D includes one or more of P, Nb, and Sr.

6. The battery cell according to any one of claims 2 to 5, characterized in that, The molecular formula is Li a M b D c O d G e In the material, the radius of the cation represented by element M is greater than that represented by element D.

7. The battery cell according to any one of claims 1 to 6, characterized in that, The structure of the lithium-containing porous material includes at least one of tetrahedral, hexahedral, and octahedral structures.

8. The battery cell according to any one of claims 1 to 7, characterized in that, The lithium-containing porous material has a structure including a first tetrahedral structure and a second tetrahedral structure. Each of the first and second tetrahedral structures independently includes at least one of silicon-oxygen tetrahedral structure, phosphorus-oxygen tetrahedral structure, aluminum-oxygen tetrahedral structure, zirconium-oxygen tetrahedral structure, and titanium-oxygen tetrahedral structure. The central atoms of the first tetrahedral structure and the second tetrahedral structure are different.

9. The battery cell according to any one of claims 1 to 8, characterized in that, The lithium-containing porous material includes: The skeleton structure includes multiple holes; A filling portion, filling at least a portion of the pores in the skeleton structure, the filling portion comprising a lithium-containing compound.

10. The battery cell according to claim 9, characterized in that, The lithium-containing porous material must satisfy at least one of the following characteristics: (1) The framework structure includes one or more of titanium dioxide, zirconium dioxide, aluminum oxide, silicon dioxide, aluminosilicate, phosphoaluminate, metal-organic framework, and covalent organic framework; (2) The lithium-containing compound includes one or more of lithium halide, lithium oxide, lithium hydroxide, and oxyacid lithium.

11. The battery cell according to any one of claims 1 to 10, characterized in that, With the positive electrode active material having a mass fraction of 100%, the lithium-containing porous material has a mass fraction of 0.05% to 1%.

12. The battery cell according to any one of claims 1 to 11, characterized in that, The positive electrode active material includes Li f Ni g Co h Mn i O j J k One or more of lithium transition metal oxides and their modified compounds, 0.5≤f≤1.2, 0.5≤g≤0.97, 0.1≤h≤0.2, 0.1≤i≤0.3, 1≤j≤2, 0≤k≤1, and J includes one or more of N, F, S and Cl.

13. The battery cell according to any one of claims 1 to 12, characterized in that, With the total mass content of the positive electrode film layer being 100%, the positive electrode film layer shall satisfy at least one of the following characteristics: (1) The mass content of the composite positive electrode active material is 60% to 90%; (2) The positive electrode film layer also includes a sulfide electrolyte, and the mass content of the sulfide electrolyte particles in the positive electrode film layer is 5% to 30%.

14. The battery cell according to any one of claims 1 to 13, characterized in that, The battery cell also includes a solid electrolyte layer, which comprises a sulfide electrolyte.

15. A composite positive electrode active material, characterized in that, It includes a positive electrode active material and a lithium-containing porous material covering at least a portion of the surface of the positive electrode active material, wherein the average pore size of the lithium-containing porous material is 0.2 nm to 0.8 nm.

16. A battery device, characterized in that, It includes multiple battery cells as described in any one of claims 1 to 14.

17. An electrical device, characterized in that, It includes multiple battery cells as described in any one of claims 1 to 14 or battery devices as described in claim 16.